Pengaruh Latihan Kekuatan Lengan Terhadap Ketepatan Shooting Game Cabang Olahraga Petanque Pada Atlet Ukm Petanque Universitas PGRI Semarang - Galang Pratama Suharto (YLPK Mahardhika, 2022)
The root of the problem in this study is that PGRI Semarang of UKM Petanque University is vulnerable to shooting. Lack of training programs and mass media often hinders athletes from improving their performance, so they are often shot primarily 9 meters away. Therefore, researchers used resistance bands and splints as training media. The question in this study was whether UPGRIS UKM petanque athlete arm strength training affected the accuracy of petanque shots, and whether there was an increase after UPGRIS UKM petanque athlete arm strength training. The purpose of this study was to determine the strength of the arm muscles for shooting accuracy in a 9 meter small business petanque distance game. The research method used is a true design of experiments exploration model type quantitative research method using a group pre-test type post-test management plan. The population and sample for this study were petanque athletes from PGRI Semarang University, for a total of eight athletes. The results showed that arm strength training increased with respect to shot accuracy, only 9 m, averaging 0.882.38 before the test, 1.5 increase after the test, and 63 increase. 02%. That is, the null hypothesis Ha is accepted based on the results. The conclusion of this study is that exercise that strengthens the arm muscles affects the accuracy of petanque shooting in the sports industry of UPGRIS athletes. The proposal uses training materials during training to extend the range up to 9m.